2020
DOI: 10.1097/jtn.0000000000000479
|View full text |Cite
|
Sign up to set email alerts
|

The Economic and Clinical Impact of an Early Mobility Program in the Trauma Intensive Care Unit: A Quality Improvement Project

Abstract: Traumatic injury survivors often face a difficult recovery. Surgical and invasive procedures, prolonged monitoring in the intensive care unit (ICU), and constant preventive vigilance by medical staff guide standards of care to promote positive outcomes. Recently, patients with traumatic injuries have benefited from early mobilization, a multidisciplinary approach to increasing participation in upright activity and walking. The purpose of this project was to determine the impact of an early mobility program in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…If diaphragm ultrasound can assist the clinician in extubating a patient sooner and reduce the ICU length of stay, this can result in considerable cost savings. A study evaluating the impact of an early mobility program in a trauma ICU suggested that a reduction in ICU length of stay of 1.31 days resulted in a cost savings of $8,239 per patient [29].…”
Section: Discussionmentioning
confidence: 99%
“…If diaphragm ultrasound can assist the clinician in extubating a patient sooner and reduce the ICU length of stay, this can result in considerable cost savings. A study evaluating the impact of an early mobility program in a trauma ICU suggested that a reduction in ICU length of stay of 1.31 days resulted in a cost savings of $8,239 per patient [29].…”
Section: Discussionmentioning
confidence: 99%
“…Inpatient mobility initiatives in their various forms are effective interventions for decreasing length of hospital stay, lessening morbidity, and improving both strength and physical function [21][22][23][24][25][26][27][28][29][30][31]. However, many of these initiatives are limited in scope or address the actions of only one specific group of unit practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Early mobilization has been demonstrated to be an effective therapeutic intervention for improving outcomes among both ICU and general medicine adult patients [21][22][23][24][25][26][27][28][29][30][31]. Prior studies consistently demonstrate decreased use of hospital resources as well as improvement in length of hospital stay, especially among patients with myocardial infarctions, total knee replacements, hip fractures, and community acquired pneumonia [24,[32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the economic and clinical impact of early mobility programs in trauma intensive care units and their impact in the reduction of patient care costs. 16 Given the success of enhanced recovery after surgery (ERAS) programs at reducing cost for a plethora of surgical procedures, [17][18][19] a similar approach can be explored for enhanced recovery of trauma patients. Clearly, the diversity of trauma patients does not permit a single unified ERAS protocol.…”
Section: Open Accessmentioning
confidence: 99%